2009
DOI: 10.1001/archgenpsychiatry.2009.1
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive and Affective Structure of Paranoid Delusions

Abstract: Both cognitive and emotion-related processes are involved in paranoid delusions. Treatment for paranoid patients should address both types of processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
102
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 268 publications
(124 citation statements)
references
References 120 publications
10
102
2
1
Order By: Relevance
“…Finally, recently published studies in patients with schizophrenia spectrum disorders have shown that delusions are directly related to impaired executive functioning [168]. However, currently there are very limited data on executive functions among patients with DD [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, recently published studies in patients with schizophrenia spectrum disorders have shown that delusions are directly related to impaired executive functioning [168]. However, currently there are very limited data on executive functions among patients with DD [14].…”
Section: Discussionmentioning
confidence: 99%
“…Bentall et al [168], in an original attempt to study delusions, used a transdiagnostic design to explore the cognitive and emotional factors related to these symptoms across schizophrenia spectrum disorders and patients with depression. Using structural equation models they concluded that both cognitive and affect-related factors contribute to the development and maintenance of delusions and that they do so in an independent manner.…”
Section: Integrative Models Of Delusionsmentioning
confidence: 99%
“…In terms of underlying information processing, depression, anxiety, and paranoia have much in common, including a heightened external locus of control (LoC), heightened anticipation and avoidance of social threat, and an underestimation of the likelihood of future positive events (Bird, Mansell, Dickens, & Tai, 2013;Bentall et al, 2009;Corcoran et al, 2006;Moutoussis, Williams, Dayan, & Bentall, 2007). These same psychological profiles are found, at attenuated levels, in nonclinical populations as shown in research adopting a mental health continuum approach Johns & Van Os, 2001;Van Os, 2003;Van et al, 2009;Verdoux & Van Os, 2002).…”
Section: Psychological Mechanisms and Urbanicitymentioning
confidence: 98%
“…This tendency is not considered to be a bias of probabilistic reasoning, since the patients are able to estimate probabilities, but rather as a data gathering bias whereby patients hastily accept hypotheses without collecting a sufficient amount of evidence to support them [121,122,123]. However, other studies have not found a ‘jumping-to-conclusions' bias to be associated with delusions [124,125]. Furthermore, a recent meta-analysis of ‘jumping-to-conclusions' studies found no support for the hypothesis that this bias plays a role in delusion formation or maintenance [126].…”
Section: Delusionsmentioning
confidence: 99%